A randomized comparative study of exteriorization of uterus versus in situ intra-peritoneal repair at cesarean delivery - Chauhan, Sapna; P. K., Syamala Devi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Various caesarean delivery techniques have been compared in the past to assess the associated short-term and long-term advantages and disadvantages. Although uterine exteriorization at caesarean section is popular among obstetricians, safety of this technique remains a disputed matter. The aim of the present study was to compare the influence of uterine exteriorization or in situ repair on caesarean section morbidity. Methods: In this prospective, randomized, controlled study, 200 pregnant women with indication for caesarean delivery were randomized as 100 patients each in the exteriorization group and in the in-situ group. Data on mean time taken for uterine incision closure, intra-operative blood loss and post-operative morbidities were collected and compared between the two groups for statistical analysis. Results: A statistically significant trend towards lesser mean time taken for the uterine wound repair was observed in the exteriorization group. However significantly more number of patients had increased post-operative pain and need for additional analgesia in exteriorization group. There was no significant difference with respect to intra-operative blood loss and incidence of nausea and vomiting; incidence of post-operative endomyometritis, febrile morbidity, wound infection, time taken for return of bowel function and length of hospital stay among the two groups. Conclusions: We concluded that uterine exteriorization and in situ repair have similar post-operative caesarean section morbidity outcomes. However, in situ repair of uterus was associated with lesser post-operative pain, and exteriorization of uterus was associated with lesser operating time.